Low-cost and high-performance poly(thienylene vinylene) derivative donor for efficient versatile organic photovoltaic cells. (September 2022) - Bi, Pengqing; Ren, Junzhen; Zhang, Shaoqing; Wang, Jianqiu; Chen, Zhihao; Gao, Mengyuan; Cui, Yong; Zhang, Tao; Qin, Jinzhao; Zheng, Zhong; Ye, Long; Hao, Xiaotao; et al.
Abstract: The utilization of donor materials with complex structures obviously increases the costs of organic photovoltaic (OPV) cells. Therefore, low-cost and high-performance are two issues that must be considered when designing polymer donors for the preparations of large-area OPV cells. Here, a poly(thienylene vinylene) derivative, named PTVT-BT was reported. PTVT-BT has a very simple completely non-fused molecular structure. PTVT-BT shows planar molecular structure and obvious solution aggregation effect. Besides, PTVT-BT demonstrates a high hole mobility up to the magnitude of 10 -2 cm -2 V -1 s -1 . The external quantum efficiency of electroluminescence of PTVT-BT is 7 × 10 -3 . As a result, the OPV cell based on PTVT-BT:eC9 demonstrates a power conversion efficiency (PCE) of 16.31%, which is the highest value among the poly(thienylene vinylene)- and polythiophene-based OPV cells. The tandem OPV cell with PTVT-BT as the donor of the sub-cell yields an outstanding PCE of 18.49%. Besides, the indoor OPV cell based on PTVT-BT:BTA3 exhibits a PCE of 27.30% under a light-emitting diode (LED) illumination of 1000 lux (2700 K). This study indicates that PTV-derivative is a kind of promising material for the future OPV industrialization. Graphical Abstract: A low-cost and high-performance PTV-derivative polymer (PTVT-BT) is designed and synthesized. PTVT-BT possesses strong crystallinity and high hole mobility. The OPV cell based on PTVT-BT:eC9 demonstrates a PCE of 16.31%. Besides, the PTVT-BT-based indoor OPV cell with 4 cm 2 effective area shows a PCE of 26.07% (1000 lux). Importantly, the tandem cell with PTVT-BT as the donor of the sub-cell exhibits an outstanding PCE of 18.49%. ga1 Highlights: A low-cost and high-performance polymer donor PTVT-BT is reported. The single and tandem OPV cells based on PTVT-BT demonstrate PCEs of 16.31% and 18.49%, respectively. The indoor OPV cell with 4 cm 2 effective area based on PTVT-BT shows a PCE over 26% (1000 lux).